Efficiency of Using Cryptocurrencies as an Investment Asset - Bondar, Mykola I.; Stovpova, Anna S.; Ostapiuk, Natalia A.; Biriuk, Olena H.; Tsiatkovska, Olena V. (International Journal of Criminology and Sociology, 2021)
The study of the effectiveness of using cryptocurrencies as an investment resource was conducted on the basis of testing the hypothesis that the introduction of leading cryptocurrencies that are components of the CRIX index into the investment portfolio improves its quality (efficiency). Cryptocurrency investment opportunities are explored on the basis of statistics for July 2016-June 2019. An average annual return on investment (ROI), which is adjusted for passive income on an investment asset (PI), is used to evaluate investment performance. In this study, cryptocurrencies are compared with the following alternative investment areas: Forex market, equities (companies with the highest weights in Nasdaq 100, Euro STOXX 50), commodities, government bonds, real estate. The criteria were determined by the increase in the Sharpe ratio of the investment portfolio and its average annual return. Optimization of investment portfolios without cryptocurrencies and with them was performed on the basis of the Markowitz model. The result shows the confirmation of the hypothesis: the introduction of 3 cryptocurrencies – Bitcoin, Ripple, Litecoin – in the proportions of 2.31%, 1%, 1%, respectively, increased the Sharpe ratio of the investment portfolio by 3.29 points, and the coefficient of return by 9.42 percentage points while increasing the risk by only 0.51 percentage points. This result indicates that the quality (increase in efficiency) of the investment portfolio due to the introduction of cryptocurrencies and the ability to control the investment risk of the portfolio despite the high volatility of cryptocurrencies. This proves the investment (speculative) function of crypto-assets, which can be the basis for developing a model of accounting for crypto-assets.